Standardization of growing substrate and irrigation appendage nutrition in rose (Rosa hybrida) cv. 'Grand Gala' (Indian Journal of Arid Horticulture, 2025)
Acclaimed as the Queen of the flowers, roses are one of the nature's beautiful creations among all the flowers. Roses are the top ranking cut flowers and are the largest traded flowers in the world and share about 51% of the world flower market. The global floriculture market is valued around US S 11-billion and India accounts for a mere 0.2% of the global export business in cut flowers and associated floricultural products. Presently, growing of flowers in our country is practiced in open field conditions. Flowers grown in open conditions are exposed to various biotic and abiotic stresses. Under such conditions, it is not possible to produce blemish free, high quality flowers in terms of bud size, stem length, lush green leaves and pests and diseases free materials which are normally produced under controlled environments in other countries. Therefore, it makes imperative to take up cut flower cultivation of roses for better quality under greenhouse conditions particularly when production of cut flower is made for export purpose.
Keywords: growing; floricultural; abiotic stresses; cultivation